The influence of blockchain technology on green entrepreneurial orientation through digital knowledge sharing among Gen Y and Gen Z entrepreneurs : A multigroup analysis - Muhammad Farhan, Jalil; Dayang Affizzah, Awang Marikan; Azlan, Ali; Mohamad, Jais (Elsevier Ltd., 2025)
Blockchain technology is transforming industries, yet its potential to drive sustainable entrepreneurship remains underexplored. This study examines how blockchain technology acceptance influences green entrepreneurial orientation among Gen Y and Gen Z entrepreneurs in Malaysia, with digital knowledge sharing as a mediating factor. Grounded in the Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB), the study evaluates the impact of perceived usefulness, perceived ease of use, attitudes, subjective norms, and perceived behavioural control on blockchain acceptance. A quantitative approach was adopted, with data collected through a structured survey of 543 Gen Y and Gen Z entrepreneurs in Malaysia. Hypotheses were tested using structural equation modelling (AMOS 21.0). Findings reveal that the identified factors positively influence blockchain acceptance, which enhances green entrepreneurial orientation through digital knowledge sharing as a complementary mediator. Moreover, Gen Z entrepreneurs exhibit a stronger inclination toward blockchain-driven sustainable practices compared to Gen Y. These results highlight the importance of blockchain technology in promoting sustainability among younger entrepreneurs. The study offers actionable insights for policymakers, educators, and technology providers to foster supportive ecosystems for blockchain-driven green entrepreneurship. It underscores blockchain’s potential as a catalyst for advancing sustainability initiatives among future-oriented entrepreneurial generations.